2023
DOI: 10.1093/cid/ciad615
|View full text |Cite
|
Sign up to set email alerts
|

Raising AWaRe-ness of Antimicrobial Stewardship Challenges in Pediatric Emergency Care: Results from the PERFORM Study Assessing Consistency and Appropriateness of Antibiotic Prescribing Across Europe

Laura Kolberg,
Aakash Khanijau,
Fabian J S van der Velden
et al.

Abstract: Objectives Optimization of antimicrobial stewardship (AMS) is key to tackling antimicrobial resistance (AMR), which is exacerbated by over-prescription of antibiotics in pediatric Emergency Departments (EDs). We described patterns of empiric antibiotic use in European EDs, and characterized appropriateness and consistency of prescribing. Methods Between August 2016 and December 2019 febrile children attending the ED in nine E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A considerable proportion of children receiving antibiotic prescriptions in EDs is evident, with reported rates ranging from 19% in Switzerland to 64% in Turkey [ 11 ]. A more recent report indicated that 46.3% of all children who attended EDs across various European countries and manifested a viral phenotype received antibiotic prescriptions, frequently involving second-line antibiotics [ 12 ]. The utilization of antibiotics invariably contributes to the development of antibacterial resistance (ABR), and prescribing antibiotics within an ED leads to extended hospital stays and increased healthcare expenditures [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A considerable proportion of children receiving antibiotic prescriptions in EDs is evident, with reported rates ranging from 19% in Switzerland to 64% in Turkey [ 11 ]. A more recent report indicated that 46.3% of all children who attended EDs across various European countries and manifested a viral phenotype received antibiotic prescriptions, frequently involving second-line antibiotics [ 12 ]. The utilization of antibiotics invariably contributes to the development of antibacterial resistance (ABR), and prescribing antibiotics within an ED leads to extended hospital stays and increased healthcare expenditures [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%